(untitled) (Bangladesh Journal of Urology, 2022)
Background: Ureterovaginal fistula is a communication between the distal ureter and the vagina. It is a rare but a relatively frequent complication of pelvic surgery. The etiological factors are very important in the treatment procedure of ureterovaginal fistula. We have very few data regarding this issue. Aim of the study: The aim of this study was to assess the etiological factors and outcome of ureterovaginal fistula in women. Methods: This was an observational study and it was conducted in Shaheed Ziaur Rahman medical College Hospital (SZMCH), Bogura, Bangladesh, during the period from May 2016 to December 2018. This study was approved by the ethical committee of the mentioned hospital. In total 48 women with ureterovaginal fistula at the center were included as the study population on the basis of non-probability purposive sampling. The investigative procedures, etiology, clinical presentation and outcomes were recorded. All the data were collected, processed, analyzed and disseminated by MS Office and SPSS version 20 as per need. Result: In analyzing the etiological factors among participants we found that, among the patients of post-hysterectomy 16.67%, 14.58%, 25% and 4.17% were with abdominal hysterectomy for fibroids, abdominal hysterectomy for malignancy, cesarean hysterectomy and rupture uterus with SVD (Spontaneous vaginal delivery). In analyzing the final outcomes among the participants we found most of the patients (n=40; 83%) healed and continent. Then 13% healed with residual incontinence and the rest 4% patients healed ureterovaginal fistula with residual vesicocervicovaginal fistula. Conclusion: In this study the emergency cesarean section was found to be commonest etiological factor and the use of abdominopelvic ultrasound was found to be effective in the confirmation of diagnosis and identifying the affected ureter. Well planned hysterectomy for benign and malignant uterine pathologies may reduce the frequencies of ureterovaginal fistula. Bangladesh J. Urol. 2021; 24(1): 72-76